Stylistic Peculiarities of Functioning of Set Expressions in Language Works by J. Salinger - Гапєєва, Ірина Миколаївна; Ісайкіна, Анастасія Олександрівна; Коваль, Оксана Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article contains the analysis of the characteristics of individual phraseological units of the author in the work of Jerome Salinger “The Catcher in The Rye”. Expressive features and functional load of phraseological collocation in the context are analyzed. Semantic-stylistic classification of the idioms in the novel is performed. Authors investigate component connections of idioms which are different in character. These connections give the text a stylistic coloring, support and intensify the general image coloring of the speech and locution expression.